Neutrophil Extracellular Traps Contain Selected Antigens of Anti-Neutrophil Cytoplasmic Antibodies - Panda, Rachita; Krieger, Thorsten; Hopf, Luke; Renné, Thomas; Haag, Friedrich; Röber, Nadja; Conrad, Karsten; Csernok, Elena; Fuchs, Tobias A. (Frontiers in Immunology, 2017)
Neutrophil extracellular traps (NETs) are chromatin filaments decorated with enzymes from neutrophil cytoplasmic granules. Anti-neutrophil cytoplasmic antibodies (ANCAs) bind to enzymes from neutrophil cytoplasmic granules and are biomarkers for the diagnosis of systemic vasculitides. ANCA diagnostics are based on indirect immunofluorescence (IIF) of ethanol-fixed neutrophils. IIF shows a cytoplasmic staining pattern (C-ANCA) due to autoantibodies against proteinase 3 (PR3) or a perinuclear staining pattern (P-ANCA) due to autoantibodies against myeloperoxidase (MPO). The distinct ANCA-staining patterns are an artifact of ethanol fixation. Here, we tested NETs as a substrate for the detection of ANCAs in human sera. We observed that P-ANCAs specifically stained NETs, while C-ANCAs targeted the cell bodies of netting neutrophils. The distinct ANCA-staining patterns were caused by the presence of MPO, but not PR3, in NETs. Using NETs as a substrate for IIF, we characterized ANCAs in sera of patients with ANCA-associated vasculitis (AAV). Furthermore, we inhibited serine proteases by diisopropylfluorophosphate to prevent chromatin unfolding and the release of NETs and thus generated neutrophils with MPO-positive nuclei and PR3-positive cytoplasm, which resembled the appearance of ethanol-fixed neutrophils. In conclusion, our data suggest that NETs are selectively loaded with antigens recognized by P-ANCAs, and netting neutrophils provide a physiological substrate for ANCA detection in patients with AAV.